Modul kebudayaan Melayu - Hj. Dora, Mohd Taib (publisher not identified, 2012)
Malay Culture module was produced to meet the needs of Malay Language Department students at Beijing Foreign Studies University. It aims to provide a basic understanding of the culture of the Malay people. The content is taken from books, the internet and other sources.